1997
DOI: 10.1128/jvi.71.9.6650-6661.1997
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure of Kunjin virus-infected cells: colocalization of NS1 and NS3 with double-stranded RNA, and of NS2B with NS3, in virus-induced membrane structures

Abstract: The subcellular location of the nonstructural proteins NS1, NS2B, and NS3 in Vero cells infected with the flavivirus Kunjin was investigated using indirect immunofluorescence and cryoimmunoelectron microscopy with monospecific antibodies. Comparisons were also made by dual immunolabelling using antibodies to double-stranded RNA (dsRNA), the putative template in the flavivirus replication complex. At 8 h postinfection, the immunofluorescent patterns showed NS1, NS2B, NS3, and dsRNA located in a perinuclear rim … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

22
294
4

Year Published

2000
2000
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 406 publications
(324 citation statements)
references
References 59 publications
22
294
4
Order By: Relevance
“…The detection of dsRNA and viral NSPs (NS1, NS2A, NS3, and NS4A) within the vesicle packets points strongly to this being the site of RNA replication (Mackenzie et al, 1998;Westaway et al, 1997b). The vesicle packets associate closely with the convoluted membranes and paracrystalline arrays, which are thought to be the sites of proteolytic processing of NS3 and NS2B (Westaway et al, 1997b). These modified membranes are linked with the ER, and ultrastructural studies have shown virions present in the ER, cytoplasmic vesicles, Golgi cisternae, and vacuoles.…”
Section: Membranes Used For Flavivirus Replication Are Provided By Thmentioning
confidence: 97%
See 3 more Smart Citations
“…The detection of dsRNA and viral NSPs (NS1, NS2A, NS3, and NS4A) within the vesicle packets points strongly to this being the site of RNA replication (Mackenzie et al, 1998;Westaway et al, 1997b). The vesicle packets associate closely with the convoluted membranes and paracrystalline arrays, which are thought to be the sites of proteolytic processing of NS3 and NS2B (Westaway et al, 1997b). These modified membranes are linked with the ER, and ultrastructural studies have shown virions present in the ER, cytoplasmic vesicles, Golgi cisternae, and vacuoles.…”
Section: Membranes Used For Flavivirus Replication Are Provided By Thmentioning
confidence: 97%
“…For historical reasons, these are called vesicular packets [reviewed in Mackenzie (2005)]. They are larger (80-to 100-nm diameter) than the 50-nm alphavirus spherules, and form from the limiting membrane of the trans-Golgi network (TGN) (Uchil and Satchidanandam, 2003;Westaway et al, 1997b). Infection by Kunjin virus leads to unique membrane structures thought to be derived from both the early and late secretory pathways.…”
Section: Membranes Used For Flavivirus Replication Are Provided By Thmentioning
confidence: 99%
See 2 more Smart Citations
“…The titre of infectious VLPs in infectious units (IUs) was determined by infection of Vero cells with 10-fold serial dilutions of the culture fluid. At 30-40 h post-infection the cells were fixed with methanol/acetone (1:1, v/v) and analysed by immunofluorescence antibody staining using the 4G4 monoclonal anti-NS1 antibody [33,34] and the 55-2F12 anti-SIV Gag monoclonal antibody (catalogue # 1610, NIH AIDS Research & Reference Reagent Program) and the number of positive cells counted using Zeiss Axiophot 2 fluorescent microscope (Carl Zeiss Microimaging GmbH, Berlin, Germany).…”
Section: Production Of Virus-like Particles (Vlps) and Determination mentioning
confidence: 99%